Probing the circumstellar medium 2.8 Gyr after the big bang: detection of Bowen fluorescence in the Sunburst arc. (15th September 2020) - Vanzella, E; Meneghetti, M; Pastorello, A; Calura, F; Sani, E; Cupani, G; Caminha, G B; Castellano, M; Rosati, P; D'Odorico, V; Cristiani, S; Grillo, C; et al.
ABSTRACT: We discovered Bowen emission arising from a strongly lensed (i.e. with magnification factor μ > 20) source hosted in the Sunburst arc at z = 2.37. We claim this source is plausibly a transient stellar object and study the unique ultraviolet lines emerging from it. In particular, narrow (σ v ≃ 40 km s −1 ) ionization lines of Fe fluoresce after being exposed to Ly α (1216 Å) radiation that pumps selectively their atomic levels. Data from VLT/MUSE, X-Shooter, and ESPRESSO observations (the latter placed at the focus of the four UTs) at increasing spectral resolution of R = 2500, 11 400, and 70 000, respectively, confirm such fluorescent lines are present since at least 3.3 yr (≃1 yr rest frame). Additional Fe forbidden lines have been detected, while C and Si doublets probe an electron density n e ≳ 10 6 cm −3 . Similarities with the spectral features observed in the circumstellar Weigelt blobs of Eta Carinae probing the circumstellar dense gas condensations in radiation-rich conditions are observed. We discuss the physical origin of the transient event, which remains unclear. We expect such transient events (including also supernova or impostors) will be easily recognized with ELTs thanks to high angular resolution provided by adaptive optics and large collecting area, especially in modest (μ < 3) magnification regime.